Transnational Sunni Pesantren and Their Socio-Political Engagement in Contemporary Indonesia - Muhammad, Hasyim; Sobirin, Mohamad; Zuhri, Mishbah Khoiruddin; Masruri, Ulin Niam (‘Abqari Journal, 2024)
The main paradigm in Sunni political theology is harmony and stability. This thinking is based on the background and tendencies of Sunni figures in the state political issues they faced at their time. Islamic boarding schools in Indonesia generally adhere to Sunni theology, including political paradigms and attitudes. Therefore, they have high attention and participation in national politics in Indonesia. Because for them, attention to and participation in national politics is an expression of the belief that love for the motherland is part of faith. In this context, new Islamic boarding schools with Sunni theology have emerged in different forms from the long-existing Sunni Islamic boarding schools. These new Islamic boarding schools have a network with the world outside and it is assumed that their establishment cannot be separated from the context of transnational Islam. Our question is, are they Educating for or Against National Political Ignorance in the midst of currents of democratization and mainstreaming of nationalism in contemporary Indonesia? The objects of this research are three transnational pesantren with Sunni theology with different international networks, namely one with a network of Saudi Arabia, one with a network of Syrian Lebanon, and one with a network of Turkey. The primary sources of this research are the results of interviews with authoritative parties in the three institutions, observations of the pesantren environment, and documentation from pesantren brochures and related documents. We found that (1) this transnational pesantren with Sunni theology only focuses on teaching Islamic education as is the case with traditional Islamic boarding schools (salafiyah), only validating the truth of their Islamic knowledge, equally pivoting on the main figure who is the reference for their knowledge, namely Sayyid Muhammad bin Alawiy Al Maliki (Haromain-Rusyaifah Islamic Boarding School), Sheikh Abdullah Al-Harariy (Shahamah-Lebanon Islamic Boarding School), and Sheikh Sulaiman Hilmi Tunahan (Sulaimaniyah Islamic Boarding School-Turkey). The three figures have written works which are made part of the compulsory curriculum for every student at the pesantren. (2) The socio-religious movement of the Lebanese Islamic Boarding Schools (Syahamah) in Indonesia is framed in the ASWAJA movement which is in line with the idea of ​​a nation-state, although in fact, their concern is more in the theological movement in the form of the conservation of the ASWAJA monotheism doctrine. As for the organizational movement of the Makah Islamic Boarding School (As-Sofwah or Haromain) it looks affirmative towards issues that link religion and the state. Meanwhile, the overall picture of the religious social movement carried out by the Turkish Islamic Boarding Schools in Indonesia shows a passive and even apathetic attitude towards the issue of Indonesian national politics.